UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA MELALUI STRATEGI PEMBELAJARAN INDEX CARD MATCH (MENCARI PASANGAN) PADA MATA PELAJARAN IPS MATERI POKOK KEGIATAN EKONOMI KELAS VII SMP SUNAN AMPEL SODUNG SUKOREJO - Ahmad Hafas Rasyidi (STKIP PGRI SITUBONDO, 2015)
This study adapted the Hopkins scheme model with 4 phases, planning, action, observation and reflection. To obtain data in this research, researcher used observation, interview and tes. Student’s learning activity observation result show the good enough improvement of this matter is visible from observation result which student activity executed at cycle I that is equal to 72,73% with the good criterion, and atobservation execution of at cycle of II being active student be promoted n very good that is equal to 92,42 %. This matter also prove that with the applying of Strategy of Study of Index of Card Match ( Searching Couple) is very good applied at student of class VII specially lesson IPS, At execution of cycle I followed by 22 student. Daily restating of cycle I show complete learn the student reach 72,73% Conclusion obtained by its result at execution of cycle I not yet succeeded hence research continued at cycle 11. Result of daily restating analysis at cycle 11 obtained complete of klasikal of equal to 86,36 % with the student efficacy of at daily restating indicate that the study with the Strategy of Study of Index of Card Match succeeding and have earned to bring the student ofresult learn which progressively mount and also shown complete learn individually with the average value > 70 and by klasikal > 80 % ketercapaian. Pursuant to research result and analyse the solution which have been conducted, inferential hence that with the applying of Strategy of Study of Index of Card Match activity and result of learning student of elementary subject IPS interest of economic activity of Anomalous class VII SMP Sunan Ampel Sodung Sukorejo Situbondo on 2014/2015 academic year is be promoted.